The effects of fiscal policy on households during the COVID-19 pandemic: Evidence from emerging economies - Dzung Bui; Lena Dräger; Bernd Hayo; Giang Hong Nghiem (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2021)
In response to the economic crisis created by the COVID-19 pandemic, many governments provided financial assistance to households. Using representative consumer surveys conducted during the pandemic in 2020, we examine the effects of this fiscal policy instrument on households in two emerging economies, Vietnam and Thailand. Our paper contributes to the literature by studying consumer sentiment and durable spending responses to government financial support and the underlying transmission channels for these responses. We find that government support improves consumer sentiment and increases the likelihood of durable spending. Possible channels for these effects include more optimistic macroeconomic expectations and higher trust in the government's ability to deal with the pandemic, as well as less concern about the general impact of the crisis. We also find that financial support improves individuals' mental health and life satisfaction. Our results suggest that government financial support not only helps stimulate the economy but also enhances people's well-being more generally.
Keywords: E62; E71; D12; D83; H31; 330; Fiscal policy; Financial support of households; Consumer sentiment; Durables spending; Expectations; Government trust; COVID-19; Thailand; Vietnam